Salt tectonics in front of the Outer Carpathian thrust wedge in the Wieliczka area (S Poland) and its exposure in the underground salt mine - Burliga, Stanisław; Krzywiec, Piotr; Dąbroś, Krzysztof; Przybyło, Jerzy; Włodarczyk, Elżbieta; Źróbek, Michał; Słotwiński, Michał (Geology, Geophysics and Environment, 2018)
Salt deposits in the Wieliczka area (Wieliczka Salt Deposit – WSD) in southern Poland comprise salt-rich strata belonging to an evaporite succession that originated in the Carpathian Foredeep basin in the Middle Miocene Badenian (Serravallian) times, ca 13.81–13.45 Ma. Although they have been mined since the 13th century and decades of investigations provided abundant data on their origin and structure, some aspects of their geological evolution are still not fully understood. This study presents current concepts on the lithostratigraphy and tectonics of the WSD. The salt-bearing facies developed near to the southern basin margin, delineated by the Carpathian orogenic front. Such a location triggered the redeposition of sediments and gravity-driven deformation followed by tectonic deformation related to the forelandward advancement of the Carpathian thrusts. As a result, the WSD consists of folds and slices composed of two main salt members: (1) the stratified salt member, with intercalating salt, sulphates and siliciclastics, and (2) the boulder salt member, built of clays with large, isolated blocks of salt. The stratified member contains abundant meso-scale tectonic structures recording the soft-sediment deformation and deformation related to the northward tectonic push exerted by the advancing Carpathian thrust wedge. The boulder member originated due to the syntectonic erosion of evaporites along the basin margins and their redeposition during progressive northward migration of the Carpathian front. Recent interpretations of seismic data imply that the WSD constitutes the core of a triangle zone developed at the contact of the Carpathian orogenic wedge with the backthrust-displaced foredeep sedimentary fill. Meso-scale examples of sedimentary and tectonic structures in the salt-bearing succession exposed in the underground Wieliczka Salt Mine are described and their formation modes discussed.